Digital Agriculture Profile: South Africa - Born, Lorna; Chirinda, Ngonidzashe; Mabaya, Edward; Afun-Ogidan, Olukemi Dolly; Girvetz, Evan Hartunian; Jarvis, Andy; Kropff, Wietske (Food and Agriculture Organization of the United Nations, 2021)
This Digital Agriculture Profile for South Africa leverages the expertise of stakeholders to evaluate the current landscape of digital agriculture in the country, including key players across the value chains, the main barriers they face, and the potential to overcome those barriers through the adoption of innovative technologies.